The use of first language in limited English proficiency classes: Good, bad or ugly? - Siti Hamin Stapa,; Abdul Hameed Abdul Majid, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
There has been an ongoing debate among language teachers on whether to use students’ first language (L1) in second language (L2) teaching. Nevertheless, the use of L1 in L2 teaching has been advocated with grounded theory as far as it merits the situation. This research article aims to investigate the effectiveness of the use of L1 to generate ideas for second language writing among low proficiency ESL learners. The study employed the experimental research design where students in the experimental group used Bahasa Melayu in generating ideas before they resumed writing their essays in English. Students in the control group used English. Two independent raters graded the essays and the scores were analysed using the paired t-test. The findings showed a marked improvement in the writing performance of students who used their first language to generate ideas before using their second language for writing. Based on the findings, we recommend that teachers encourage the use of first language before writing or composing in English especially among low-level proficiency ESL learners